New Findings on Impact Variation From the Head Start Impact Study: Informing the Scale-Up of Early Childhood Programs. (April 2018) - Morris, Pamela A.; Connors, Maia; Friedman-Krauss, Allison; McCoy, Dana Charles; Weiland, Christina; Feller, Avi; Page, Lindsay; Bloom, Howard; Yoshikawa, Hirokazu
This article synthesizes findings from a reanalysis of data from the Head Start Impact Study with a focus on impact variation. This study addressed whether the size of Head Start's impacts on children's access to center-based and high-quality care and their school readiness skills varied by child characteristics, geographic location, and the experiences of children in the control group. Across multiple sets of analyses based on new, innovative statistical methods, findings suggest that the topline Head Start Impact Study results of Head Start's average impacts mask substantial variation in its effectiveness and that one key source of that variation was in the counterfactual experiences and the context of Head Start sites (as well as the more typically examined child characteristics; e.g., children's dual language learner status). Implications are discussed for the future of Head Start and further research, as well as the scale-up of other early childhood programs, policies, and practices.